A profile of 2008 Olympic Taekwondo competitors - Kazemi, Mohsen (Canadian Chiropractic Association, 2010)
The purpose of this study was to identify the characteristics of Olympic medal winners (gold, silver, bronze) who competed in the 2008 Beijing Olympic Games and compare these characteristics to those who competed but did not earn medals. We have also descriptively analysed the 2008 data in comparison to the 2004 data (Kazemi et al., 2009), and 2000 data (Kazemi et al., 2006) and summarized changes that were identified. This study as well as the last two studies did not find any statistically significant differences between winners and non-winners with regards to average age, weight, height and BMI. There are, however, some trends that were observed. Female winners were slightly younger, shorter, with greater BMI’s versus non-winners. There was a significant decrease in frequency of warnings from 2004 to 2008. Unlike 2004, the 2008 Olympic Taekwondo competitors used more defensive kicks to score. These suggest a shift from aggressive tactics to score to a more conservative one.